LEGAL ANALYSIS OF LEGAL PROTECTION OF THE RIGHTS OF CHILD VICTIMS OF EARLY MARRIAGE - Fadlan; Muhammad Sabir Rahman; Sunardi Purwanda; Bakhtiar Tijjang; Kairuddin Karim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine and analyze the positive legal regulations in Indonesia regarding the protection of the rights of children who are victims of early marriage and the forms of legal protection for children who are victims of early marriage. This research uses a normative research method with a legislative approach and an analytical approach. The legal sources used are primary, secondary, and tertiary legal materials. The legal analysis will be conducted using a qualitative prescriptive approach. The results of this study are Positive Legal Regulations or Those Applicable in Indonesia Regarding the Protection of the Rights of Children Who Are Victims of Early Marriage, namely Law No. 16 of 2019 concerning Marriage (the latest age of marriage is 19 years old, strict supervision and assessment of dispensation requests and children's opinions must be heard in marriage dispensation requests), Law No. 35 of 2014 concerning Child Protection (the maximum age of children is 18 years old, affirmation of children, protected children's rights, parental obligations to prevent early marriage and special protection mechanisms as well as recovery mechanisms and criminal sanctions, especially for parents who force children to enter into early marriage) and Law 12 of 2022 concerning Criminal Acts of Sexual Violence (forced marriage is sexual violence and recovery of children's rights if in early marriage the child becomes a victim according to the provisions of this Law) and Forms of Legal Protection for Children Who Are Victims of Early Marriage, namely preventive legal protection (minimum age of 19 years for marriage and the obligation to prevent by parents and the state), repressive legal protection (legal and criminal responsibility for parents or parties who force marriage, the existence of sexual violence and exploitation in early marriage), legal protection in the form of restoration and fulfillment of rights and protection of administrative and civil law (tightening and accuracy in granting marriage dispensations and marriage annulments).